The teaching of mathematics, a challenge for teachers of XXI century - Guillermo López-Quijano (Corporación Universitaria Minuto de Dios, 2014)
This article is, in the first part, about the problems that teachers, students and parents face when they embark on the process of teaching and learning of mathematics, and about the difficulties that the learner encounters throughout his or her educational life in which he or she applies mathematical knowledge in solving environmental problems. The second part presents a didactics and pedagogical proposal which aims at assessing the social-academic attitude of the student during the learning of mathematics among students of Rafael Uribe Technical School from Toca municipality. The proposal involves four aspects: the collaborative learning environment, the didactic system based on problem-solving, the characteristics of the specialized classroom and the formative assessment. Lastly, the results obtained from this type of research, systematization of Teaching experiences, from an attitudinal, emotional, and social - academic aspect of the student.